Effect of supplementing vitamin E analogues on post-thaw semen parameters and fertility in chicken. Issue 3 (4th May 2019) - Pranay Kumar, K.; Swathi, B.; Shanmugam, M.
ABSTRACT: 1. The effect of supplementing water-soluble vitamin E analogues 6-hydroxy-2, 5, 7, 8-tetramethylchromane-2-carboxylic acid (trolox) and butylated hydroxy toluene (BHT) was studied in two separate experiments. 2. In the first experiment, trolox was supplemented at 0.2 mM, 0.4 mM and 0.8 mM concentrations along with N-methylacetamide (MA; 12% final concentration) and semen was cryopreserved in 0.5 ml French straws. Different semen parameters and fertility were assessed from post-thaw samples. 3. Sperm motility, live sperm, and mitochondrial activity were significantly lower ( P < 0.05) in cryopreserved semen. Lipid peroxidation (LPO) was significantly higher ( P < 0.05) in cryopreserved semen that was reduced by trolox supplementation. The treatment containing trolox at 0.2 mM concentration produced significantly higher ( P < 0.05) fertility compared to unsupplemented cryopreservation treatment. 4. In the second experiment, BHT was supplemented at 0.25 mM, 0.5 mM, and 1 mM concentrations along with MA during semen cryopreservation. 5. Sperm motility, live sperm and MTT dye reduction test were significantly lower ( P < 0.05) in cryopreserved semen. These parameters declined with increasing BHT concentration. Abnormal sperm was significantly higher ( P < 0.05) in the BHT supplemented treatments. The sperm chromatin dispersion (SCD) test was significantly higher ( P < 0.05) in cryopreserved samples and was highest in samples supplemented with 0.5 mM and 1 mM BHT. The percentage fertility was significantly lower ( P < 0.05) in cryopreserved semen and BHT supplementation did not improve fertility. 6. In conclusion, trolox supplementation at 0.2 mM concentration during semen cryopreservation improved fertility, whereas BHT supplementation resulted in a decline in post-thaw semen parameters.